Iowa RBA, December 3, 19-24, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Six emails of Iowa RBA updates for December 3, 19-24, 1999. Highlights of the updates include sightings of a Yellow-billed Loon, Long-tailed Duck, Bullock's Oriole, Black Scoter, and a Thayer's Gull. Epson - sheet feed/flatbed